Development of Ex-Ante Analysis Method on Socio-Economic Impact of Infrastructure Project - Hengki Purwoto; Rachmawan Budhiarto; Derajad Sulistyo Widhyharto; Juhri Iwan Agriawan; Dwi Ardianta Kurniawan; Joewono Soemardjito; Hafid Lastito; Jagad Hidayat Jati; Dwi Novitasari (Journal of Infrastructure Policy and Management (JIPM), 2020)
The increasing need for infrastructure development in order to encourage economic growth and improve people’s lives requires proper planning so that the expected benefits can be achieved. PT PII is expected to play an important role in improving the quality of infrastructure projects, not only in the form of providing guarantees but also through improving the quality of project preparation, transactions and implementation, in accordance with best practices that benefit all stakeholders. This paper aims to present the results of research into the development of an economic and social impact analysis model of PPP and Non-PPP infrastructure projects using quantitative and qualitative approach. The study examines 3 PPP projects that have specific service characteristics, namely: air transportation, public street lighting, and special economic zones. The economic impact analysis model used in the analysis uses the impact measurement attributes according to the characteristics of the infrastructure services. Social impact measurement uses an index developed to determine the response of the community to PPP infrastructure project plans. The results of the study indicate that the development of the Komodo Airport and the Mandalika Special Economic Zone are expected to have a positive impact on regional development, especially in tourism activities, while the public street lighting projects have an impact on improving traffic safety and environmental comfort in the city.